Hutātmā Dāmodara Hari Cāpekara yāñce ātmavrtta - Chapekar, Damodar Hari, 1869-1898 (Mahārāshṭra Rājya Sāhitya āṇi Sãskrti Maṇḍaḷa, 1974)
An autobiographical account of an Indian revolutionary who was hanged in 1898 for assassinating a British officer in Poona.